A 5-DOF Model for Aeroengine Spindle Dual-rotor System Analysis - HU, Qinghua; DENG, Sier; TENG, Hongfei (Chinese journal of aeronautics, 2011)
This paper develops a five degrees of freedom（5-DOF） model for aeroengine spindle dual-rotor system dynamic analysis.In this system,the dual rotors are supported on two angular contact ball bearings and two deep groove ball bearings,one of the latter-mentioned bearings works as the inter-shaft bearing.Driven by respective motors,the dual rotors have different co-rotating speeds.The proposed model mathematically formulates the nonlinear displacements,elastic deflections and contact forces of bearings with consideration of 5-DOF and coupling of dual rotors.The nonlinear equations of motions of dual rotors with 5-DOF are solved using Runge-Kutta-Fehlberg algorithm.In order to investigate the effect of the introduced 5-DOF and nonlinear dy-namic bearing model,we compare the proposed model with two models：the 3-DOF model of this system only considering three translational degrees of freedom（Gupta,1993,rotational freedom is neglected）;the 5-DOF model where the deep groove ball bearings are simplified as linear elastic spring（Guskov,2007）.The simulation results verify Gupta＇s prediction（1993） and show that the rotational freedom of rotors and nonlinear dynamic model of bearings have great effect on the system dynamic simula-tion.The quantitative results are given as well.